2019
DOI: 10.1080/14766825.2019.1694534
|View full text |Cite
|
Sign up to set email alerts
|

Utopian resort living: islands of reclamation and environmental resistance in Bali and Western Australia

Abstract: This article provides a comparative analysis of localized contests over the reclamation of new islands for resort-style development projects in waters near tourist destinations in Bali and Western Australia. The research focuses on the Tirta Wahana Bali Internasional Resort proposed for a seabed site in Benoa Bay, Bali, and the North Port Quay development proposed for a seabed site off the coast of Fremantle, Western Australia. The investigation finds that proximity plays a common critical role in the shaping … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Bali is currently facing serious economic, social, water shortages, water inequity, widespread sewage pollution, and biodiversity and habitat loss. (Kerr & Wardana, 2019). The number of tourists that continue to increase has not significantly maintained the sustainability of the LPD and is even more damaging (Adityanandana & Gerber, 2019).…”
Section: Vol 22 No 184/ Oct 2021 Access To Successmentioning
confidence: 99%
“…Bali is currently facing serious economic, social, water shortages, water inequity, widespread sewage pollution, and biodiversity and habitat loss. (Kerr & Wardana, 2019). The number of tourists that continue to increase has not significantly maintained the sustainability of the LPD and is even more damaging (Adityanandana & Gerber, 2019).…”
Section: Vol 22 No 184/ Oct 2021 Access To Successmentioning
confidence: 99%
“…The acceleration of material and immaterial transformations to increase the accommodation capacity and location branding is causing conflicts in many mass tourist destinations. Against what is often defined as overtourism (Dodds and Butler, 2019;Milano et al, 2019;Perkumienė and Pranskūnienė, 2019;Seraphin et al, 2018), forms of resistance have been reported worldwide: from Oceania and South-Eastern Asia (Kerr and Wardana, 2019;Camisani, 2018;Winengan, 2019) to Latin America (Loperena, 2017), from Northern (Oklevik et al, 2019;Stanley, 2020) to Central (Smith et al, 2019) and Southern Europe (Schiermeier, 2004;Carballo et al, 2019;García-Hernández et al, 2017;Ioannides et al, 2016;Navarro-Jurado et al, 2019). More detailed insights might come from the real-time observation of oppositional movements 1 .…”
Section: Introductionmentioning
confidence: 99%